Comparative genomic analysis of Cluster AZ Arthrobacter phages - Freise, Amanda; Furlong, Kieran; Klyczek, Karen; Beyer, Andréa; Chong, Rebecca; Edgington, Nicholas; Gibb, Bryan; Swerdlow, Sarah; Bendele, Madison; Cobb, Isobel; Mitchell, Zachary; Cresawn, Steven; et al. (bioRxiv (Cold Spring Harbor Laboratory), 2025)
Abstract Bacteria in the Arthrobacter genus belong to the phylum Actinobacteria and are primarily soil-dwelling. Over 600 bacteriophages infecting Arthrobacter hosts have been isolated and sequenced, and genomic analyses show these phages to be highly diverse with mosaic genome architectures. We describe here a group of 32 Arthrobacter phages grouped in Cluster AZ, isolated on four different Arthrobacter strains all with siphoviral morphologies. The Cluster AZ phages exhibit a spectrum of diversity and can be subdivided into four subclusters. The diversity in minor tail protein and endolysin genes correlates partly with isolation host strain and may be predictive of the host range of these phages. Most of the Cluster AZ phages are temperate, form stable lysogens, and encode an integrase; however, an immunity repressor gene has not been identified. The intracluster diversity was analyzed in-depth at the whole genome level and through individual genes. As more Arthrobacter phages are isolated and analyzed they continue to provide new insights into phage evolution.
Keywords: Arthrobacter; Bacteria; Biology; Cluster (spacecraft); Computational biology; Computer science; Genetics; dept.bio

Whole genome comparison of a large collection of mycobacteriophages reveals a continuum of phage genetic diversity - Pope, Welkin H; Bowman, Charles A; Russell, Daniel A; Jacobs-Sera, Deborah; Asai, David J; Cresawn, Steven G; Jacobs, Jr, William R; Hendrix, Roger W; Lawrence, Jeffrey G; Hatfull, Graham F; Science Education Alliance Phage Hunters Advancing Genomics and Evolutionary Science; Phage Hunters Integrating Research and Education; et al. (eLife, 2015)
The bacteriophage population is large, dynamic, ancient, and genetically diverse. Limited genomic information shows that phage genomes are mosaic, and the genetic architecture of phage populations remains ill-defined. To understand the population structure of phages infecting a single host strain, we isolated, sequenced, and compared 627 phages of Mycobacterium smegmatis. Their genetic diversity is considerable, and there are 28 distinct genomic types (clusters) with related nucleotide sequences. However, amino acid sequence comparisons show pervasive genomic mosaicism, and quantification of inter-cluster and intra-cluster relatedness reveals a continuum of genetic diversity, albeit with uneven representation of different phages. Furthermore, rarefaction analysis shows that the mycobacteriophage population is not closed, and there is a constant influx of genes from other sources. Phage isolation and analysis was performed by a large consortium of academic institutions, illustrating the substantial benefits of a disseminated, structured program involving large numbers of freshman undergraduates in scientific discovery.
Keywords: bacteriophage; dept.bio; evolution; genomic; peer-reviewed

Cluster M mycobacteriophages Bongo, PegLeg, and Rey with unusually large repertoires of tRNA isotypes - Pope, Welkin H; Anders, Kirk R; Baird, Madison A; Bowman, Charles A; Boyle, Michelle M; Broussard, Gregory W; Chow, Tiffany W; Clase, Kari; Cooper, Shannon D; Cornely, Kathleen; Dejong, Randall J; Delesalle, Veronique A; et al. (Journal of Virology, 2014)
Genomic analysis of a large set of phages infecting the common host Mycobacterium smegmatis mc2155 shows that they span considerable genetic diversity. There are more than 20 distinct types that lack nucleotide similarity with each other, and there is considerable diversity within most of the groups. Three newly isolated temperate mycobacteriophages, Bongo, PegLeg, and Rey, constitute a new group (cluster M), with the closely related phages Bongo and PegLeg forming subcluster M1 and the more distantly related Rey forming subcluster M2. The clusterMmycobacteriophages have siphoviral morphologies with unusually long tails, are homoimmune, and have larger than average genomes (80.2 to 83.7 kbp). They exhibit a variety of features not previously described in other mycobacteriophages, including noncanonical genome architectures and several unusual sets of conserved repeated sequences suggesting novel regulatory systems for both transcription and translation. In addition to containing transfer-messenger RNA and RtcB-like RNA ligase genes, their genomes encode 21 to 24 tRNA genes encompassing complete or nearly complete sets of isotypes. We predict that these tRNAs are used in late lytic growth, likely compensating for the degradation or inadequacy of host tRNAs. They may represent a complete set of tRNAs necessary for late lytic growth, especially when taken together with the apparent lack of codons in the same late genes that correspond to tRNAs that the genomes of the phages do not obviously encode. © 2014, American Society for Microbiology.
40 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/014-261-678-659-153 tex.type: [object Object]
Keywords: Base Composition; Base Sequence; Codon; Conserved Sequence; DNA binding motif; DNA sequence; Gene Order; Genome Size; Genome; Viral; Inverted Repeat Sequences; Lysogeny; Multigene Family; Mycobacteriophages; Mycobacterium smegmatis; Open Reading Frames; Phylogeny; RNA cleavage; RNA degradation; RNA translation; RNA; Transfer; RNA; Viral; Repetitive Sequences; Nucleic Acid; Sequence Alignment; Virion; Virus Assembly; article; controlled study; dept.bio; gene cassette; gene control; gene structure; genetic analysis; genetic transcription; genetic variability; membrane protein; mycobacteriophage; mycobacteriophage Bongo; mycobacteriophage M; mycobacteriophage Pegleg; mycobacteriophage Rey; nonhuman; nucleotide sequence; priority journal; protein gp19; protein gp23; protein gp24; protein gp26; protein gp30; protein gp31; protein gp39; single stranded DNA binding protein; tmp gene; transfer RNA; unclassified drug; viral genetics; virus assembly; virus classification; virus immunity; virus morphology

Prophage-mediated defence against viral attack and viral counter-defence. - Dedrick, Rebekah M; Jacobs-Sera, Deborah; Bustamante, Carlos A Guerrero; Garlena, Rebecca A; Mavrich, Travis N; Pope, Welkin H; Reyes, Juan C Cervantes; Russell, Daniel A; Adair, Tamarah; Alvey, Richard; Bonilla, J Alfred; Bricker, Jerald S; et al. (Nature Microbiology, 2017)
Temperate phages are common, and prophages are abundant residents of sequenced bacterial genomes. Mycobacteriophages are viruses that infect mycobacterial hosts including Mycobacterium tuberculosis and Mycobacterium smegmatis, encompass substantial genetic diversity and are commonly temperate. Characterization of ten Cluster N temperate mycobacteriophages revealed at least five distinct prophage-expressed viral defence systems that interfere with the infection of lytic and temperate phages that are either closely related (homotypic defence) or unrelated (heterotypic defence) to the prophage. Target specificity is unpredictable, ranging from a single target phage to one-third of those tested. The defence systems include a single-subunit restriction system, a heterotypic exclusion system and a predicted (p)ppGpp synthetase, which blocks lytic phage growth, promotes bacterial survival and enables efficient lysogeny. The predicted (p)ppGpp synthetase coded by the Phrann prophage defends against phage Tweety infection, but Tweety codes for a tetrapeptide repeat protein, gp54, which acts as a highly effective counter-defence system. Prophage-mediated viral defence offers an efficient mechanism for bacterial success in host-virus dynamics, and counter-defence promotes phage co-evolution.
175 citations (Crossref) [2023-10-31] Place: England Dedrick, Rebekah M. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Jacobs-Sera, Deborah. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Bustamante, Carlos A Guerrero. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Garlena, Rebecca A. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Mavrich, Travis N. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Pope, Welkin H. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Reyes, Juan C Cervantes. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Russell, Daniel A. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Adair, Tamarah. Department of Biology, Baylor University, Waco, Texas 76798, USA. Alvey, Richard. Biology Department, Illinois-Wesleyan University, Bloomington, Illinois 61702, USA. Bonilla, J Alfred. Biology Department, University of Wisconsin-River Falls, River Falls, Wisconsin 54016, USA. Bricker, Jerald S. Biology Department, Nebraska-Wesleyan University, Lincoln, Nebraska 68504, USA. Brown, Bryony R. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Byrnes, Deanna. Biology Department, Carthage College, Kenosha, Wisconsin 53140, USA. Cresawn, Steven G. Biology Department, James Madison University, Harrisonburg, Virginia 22807, USA. Davis, William B. School of Molecular Biosciences, Washington State University Pullman, Washington 99164, USA. Dickson, Leon A. Department of Biology, Howard University, Washington, Washington DC 20059, USA. Edgington, Nicholas P. Biology Department, Southern Connecticut State University, New Haven, Connecticut 06515, USA. Findley, Ann M. Biology, School of Sciences, University of Louisiana at Monroe, Monroe, Louisiana 71209, USA. Golebiewska, Urszula. Biological Sciences and Geology, Queensborough Community College, Bayside, New York 11364, USA. Grose, Julianne H. Biology Department, Brigham Young University, Provo, Utah 84602, USA. Hayes, Cory F. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Hughes, Lee E. Biological Sciences, University of North Texas, Denton, Texas 76203, USA. Hutchison, Keith W. Molecular and Biomedical Sciences, University of Maine, Honors College, Orono, Maine 04469, USA. Isern, Sharon. Department of Biological Sciences, Florida Gulf Coast University, Fort Myers, Florida 33965, USA. Johnson, Allison A. Biology Department, Virginia Commonwealth University, Richmond, Virginia 23284, USA. Kenna, Margaret A. Biological Sciences, Lehigh University, Bethlehem, Pennsylvania 18015, USA. Klyczek, Karen K. Biology Department, University of Wisconsin-River Falls, River Falls, Wisconsin 54016, USA. Mageeney, Catherine M. Biological Sciences, Lehigh University, Bethlehem, Pennsylvania 18015, USA. Michael, Scott F. Department of Biological Sciences, Florida Gulf Coast University, Fort Myers, Florida 33965, USA. Molloy, Sally D. Molecular and Biomedical Sciences, University of Maine, Honors College, Orono, Maine 04469, USA. Montgomery, Matthew T. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Neitzel, James. Biology Department, The Evergreen State College, Olympia, Washington 98502, USA. Page, Shallee T. Division of Environmental and Biological Sciences, University of Maine-Machias, Machias, Maine 04654, USA. Pizzorno, Marie C. Biology Department, Bucknell University, Lewisburg, Pennsylvania 17837, USA. Poxleitner, Marianne K. Biology Department, Gonzaga University, Spokane, Washington 99258, USA. Rinehart, Claire A. Biology Department, Western Kentucky University, Bowling Green, Kentucky 42101, USA. Robinson, Courtney J. Department of Biology, Howard University, Washington, Washington DC 20059, USA. Rubin, Michael R. Biology Department, University of Puerto Rico-Cayey, Cayey, Puerto Rico 00736, USA. Teyim, Joseph N. Biological Sciences, Lehigh University, Bethlehem, Pennsylvania 18015, USA. Vazquez, Edwin. Biology Department, University of Puerto Rico-Cayey, Cayey, Puerto Rico 00736, USA. Ware, Vassie C. Biological Sciences, Lehigh University, Bethlehem, Pennsylvania 18015, USA. Washington, Jacqueline. Department of Biology and Chemistry, Nyack College, Nyack, New York 10960, USA. Hatfull, Graham F. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA.
Keywords: *Mycobacteriophages/ph [Physiology]; *Mycobacterium smegmatis/vi [Virology]; *Mycobacterium tuberculosis/vi [Virology]; *Prophages/ph [Physiology]; DNA; Viral; DNA; Viral/ge [Genetics]; Genetic Variation; Genome; Bacterial; Genome; Viral; Ligases; Ligases/ge [Genetics]; Lysogeny; Mycobacteriophages; Mycobacteriophages/ge [Genetics]; Mycobacterium smegmatis; Mycobacterium smegmatis/ge [Genetics]; Mycobacterium tuberculosis; Mycobacterium tuberculosis/ge [Genetics]; Phylogeny; Prophages; Prophages/en [Enzymology]; Prophages/ge [Genetics]; Viral Proteins; Viral Proteins/ge [Genetics]; bacterial genome; dept.bio; enzymology; genetic variation; genetics; guanosine 3'; 5'-polyphosphate synthetases; ligase; lysogenization; mycobacteriophage; phylogeny; physiology; prophage; viral protein; virology; virus DNA; virus genome

Genome sequences of Chancellor, Mitti, and Wintermute, three subcluster K4 phages isolated using Mycobacterium smegmatis mc ^2 155 - Edgington, Nicholas P.; Voshell, Stephanie M.; Ware, Vassie C.; Akoto, Francis F.; Alhout, Alexa A.; Atwal, Gurvina J.; Balyozian, John B.; Cadieux, Zachary A.; Chop, Brianna M.; Cresawn, Steven G.; Cudkevich, Netta; Faltine-Gonzalez, Dylan Z.; et al. (Genome Announcements, 2017)
Mycobacteriophages Chancellor, Mitti, and Wintermute infect Mycobacterium smegmatis mc2155 and are closely related to phages Cheetobro and Fionnbharth in subcluster K4. Genome sizes range from 57,697 bp to 58,046 bp. Phages are predicted to be temperate and to infect the pathogen Mycobacterium tuberculosis. © 2017 Edgington et al.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-598-311-527-674, pop00117 tex.type: [object Object]
Keywords: Mycobacterium smegmatis; Mycobacterium tuberculosis; dept.bio; genome size; infectious agent; mycobacteriophage; nonhuman

Genomic diversity of bacteriophages infecting Microbacterium spp. - Jacobs-Sera, Deborah; Abad, Lawrence A; Alvey, Richard M; Anders, Kirk R; Aull, Haley G; Bhalla, Suparna S; Blumer, Lawrence S; Bollivar, David W; Bonilla, J Alfred; Butela, Kristen A; Coomans, Roy J; Cresawn, Steven G; et al. (PloS one, 2020)
The bacteriophage population is vast, dynamic, old, and genetically diverse. The genomics of phages that infect bacterial hosts in the phylum Actinobacteria show them to not only be diverse but also pervasively mosaic, and replete with genes of unknown function. To further explore this broad group of bacteriophages, we describe here the isolation and genomic characterization of 116 phages that infect Microbacterium spp. Most of the phages are lytic, and can be grouped into twelve clusters according to their overall relatedness; seven of the phages are singletons with no close relatives. Genome sizes vary from 17.3 kbp to 97.7 kbp, and their G+C% content ranges from 51.4% to 71.4%, compared to ~67% for their Microbacterium hosts. The phages were isolated on five different Microbacterium species, but typically do not efficiently infect strains beyond the one on which they were isolated. These Microbacterium phages contain many novel features, including very large viral genes (13.5 kbp) and unusual fusions of structural proteins, including a fusion of VIP2 toxin and a MuF-like protein into a single gene. These phages and their genetic components such as integration systems, recombineering tools, and phage-mediated delivery systems, will be useful resources for advancing Microbacterium genetics.
39 citations (Crossref) [2023-10-31] Place: United States Jacobs-Sera, Deborah. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Abad, Lawrence A. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Alvey, Richard M. Department of Biology, Illinois Wesleyan University, Bloomington, Illinois, United States of America. Anders, Kirk R. Department of Biology, Gonzaga University, Spokane, Washington, United States of America. Aull, Haley G. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Bhalla, Suparna S. Department of Natural Sciences, Mount Saint Mary College, Newburgh, New York, United States of America. Blumer, Lawrence S. Department of Biology, Morehouse College, Atlanta, Georgia, United States of America. Bollivar, David W. Department of Biology, Illinois Wesleyan University, Bloomington, Illinois, United States of America. Bonilla, J Alfred. Department of Biology, University of Wisconsin-River Falls, River Falls, Wisconsin, United States of America. Butela, Kristen A. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Coomans, Roy J. Department of Biology, North Carolina A&T State University, Greensboro, North Carolina, United States of America. Cresawn, Steven G. Department of Biology, James Madison University, Harrisonburg, Virginia, United States of America. D'Elia, Tom. Department of Biological Sciences, Indian River State College, Fort Pierce, Florida, United States of America. Diaz, Arturo. Department of Biology, La Sierra University, Riverside, California, United States of America. Divens, Ashley M. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Edgington, Nicholas P. Department of Biology, Southern Connecticut State University, New Haven, Connecticut, United States of America. Frederick, Gregory D. Department of Biology and Kinesiology, LeTourneau University, Longview, Texas, United States of America. Gainey, Maria D. Department of Chemistry & Physics, Western Carolina University, Cullowhee, North Carolina, United States of America. Garlena, Rebecca A. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Grant, Kenneth W. Department of Pathology, Wake Forest Baptist Health, Winston-Salem, North Carolina, United States of America. Gurney, Susan M R. Department of Biology, Drexel University, Philadelphia, Pennsylvania, United States of America. Hendrickson, Heather L. School of Natural and Computational Sciences, Massey University, Auckland, New Zealand. Hughes, Lee E. Department of Biological Sciences, University of North Texas, Denton, Texas, United States of America. Kenna, Margaret A. Department of Biological Sciences, Lehigh University, Bethlehem, Pennsylvania, United States of America. Klyczek, Karen K. Department of Biology, University of Wisconsin-River Falls, River Falls, Wisconsin, United States of America. Kotturi, Hari. Department of Biology, University of Central Oklahoma, Edmond, Oklahoma, United States of America. Mavrich, Travis N. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. McKinney, Angela L. Department of Biology, Nebraska Wesleyan University, Lincoln, Nebraska, United States of America. Merkhofer, Evan C. Department of Natural Sciences, Mount Saint Mary College, Newburgh, New York, United States of America. Moberg Parker, Jordan. Department of Microbiology, Immunology, & Molecular Genetics, University of California, Los Angeles, California, United States of America. Molloy, Sally D. Department of Molecular and Biomedical Sciences, University of Maine, Orono, Maine, United States of America. Monti, Denise L. Department of Biology, University of Alabama at Birmingham, Birmingham, Alabama, United States of America. Pape-Zambito, Dana A. Department of Biological Sciences, University of the Sciences in Philadelphia, Philadelphia, Pennsylvania, United States of America. Pollenz, Richard S. Department Cell Biology, Microbiology and Molecular Biology, University of South Florida, Tampa, Florida, United States of America. Pope, Welkin H. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Reyna, Nathan S. Department of Biology, Ouachita Baptist University, Arkadelphia, Arkansas, United States of America. Rinehart, Claire A. Department of Biology, Western Kentucky University, Bowling Green, Kentucky, United States of America. Russell, Daniel A. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Shaffer, Christopher D. Department of Biology, University of Washington in St. Louis, St. Louis, Missouri, United States of America. Sivanathan, Viknesh. Howard Hughes Medical Institute, Chevy Chase, Maryland, United States of America. Stoner, Ty H. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Stukey, Joseph. Biology Department, Hope College, Holland, Michigan, United States of America. Sunnen, C Nicole. Department of Biological Sciences, University of the Sciences, Philadelphia, Pennsylvania, United States of America. Tolsma, Sara S. Biology Department, Northwestern College, Orange City, Iowa, United States of America. Tsourkas, Philippos K. School of Life Sciences, University of Nevada, Las Vegas, Las Vegas, Nevada, United States of America. Wallen, Jamie R. Department of Chemistry & Physics, Western Carolina University, Cullowhee, North Carolina, United States of America. Ware, Vassie C. Department of Biological Sciences, Lehigh University, Bethlehem, Pennsylvania, United States of America. Warner, Marcie H. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Washington, Jacqueline M. Department of Natural Sciences, Nyack College, Nyack, New York, United States of America. Westover, Kristi M. Department of Biology, Winthrop University, Rock Hill, South Carolina, United States of America. Whitefleet-Smith, JoAnn L. Department of Biology & Biotechnology, Worcester Polytechnic Institute, Worcester, Massachusetts, United States of America. Wiersma-Koch, Helen I. Department of Biological Sciences, Indian River State College, Fort Pierce, Florida, United States of America. Williams, Daniel C. Department of Biology, Coastal Carolina University, Conway, South Carolina, United States of America. Zack, Kira M. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Hatfull, Graham F. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America.
Keywords: *Actinobacteria/vi [Virology]; *Bacteriophages/ge [Genetics]; *Genetic Variation; *Genome; Viral; Actinobacteria; Article; Bacteriophages; Bacteriophages/cl [Classification]; Bacteriophages/ip [Isolation & Purification]; Base Composition; DNA base composition; DNA; Viral; DNA; Viral/ge [Genetics]; Genes; Viral; Genetic Variation; Genome; Viral; Genomics; Microbacterium; MuF like protein; Phylogeny; VIP2 toxin; Viral Fusion Proteins; Viral Fusion Proteins/ge [Genetics]; bacterial genome; bacterial strain; bacterial toxin; bacteriophage; capsid protein; classification; comparative genomics; controlled study; dept.bio; fusion protein; gene sequence; genetic variability; genetic variation; genetics; genome size; genomics; isolation and purification; nonhuman; nucleotide sequence; peer-reviewed; phylogeny; unclassified drug; virology; virus DNA; virus fusion protein; virus gene; virus genome; virus infection; virus isolation

Models of classroom assessment for course-based research experiences - Hanauer, David I.; Zhang, Tong; Graham, Mark J.; Adams, Sandra D.; Ahumada-Santos, Yesmi Patricia; Alvey, Richard M.; Antunes, Mauricio S.; Ayuk, Mary A.; Elena Báez-Flores, María; Bancroft, Christa T.; Bates, Tonya C.; Bechman, Meghan J.; et al. (Frontiers in Education, 2023)
Course-based research pedagogy involves positioning students as contributors to authentic research projects as part of an engaging educational experience that promotes their learning and persistence in science. To develop a model for assessing and grading students engaged in this type of learning experience, the assessment aims and practices of a community of experienced course-based research instructors were collected and analyzed. This approach defines four aims of course-based research assessment—(1) Assessing Laboratory Work and Scientific Thinking; (2) Evaluating Mastery of Concepts, Quantitative Thinking and Skills; (3) Appraising Forms of Scientific Communication; and (4) Metacognition of Learning—along with a set of practices for each aim. These aims and practices of assessment were then integrated with previously developed models of course-based research instruction to reveal an assessment program in which instructors provide extensive feedback to support productive student engagement in research while grading those aspects of research that are necessary for the student to succeed. Assessment conducted in this way delicately balances the need to facilitate students’ ongoing research with the requirement of a final grade without undercutting the important aims of a CRE education.
Keywords: dept.bio; peer-reviewed